2001
DOI: 10.1542/peds.107.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cerebral Cortical Gray Matter Growth After Treatment With Dexamethasone for Neonatal Chronic Lung Disease

Abstract: The data suggest an impairment in brain growth, principally affecting cerebral cortical gray matter, secondary to systemic dexamethasone therapy. Although the premature infants who received dexamethasone were smaller with more severe respiratory disease, these findings are consistent with growing evidence of a potential deleterious effect of dexamethasone on neonatal brain and subsequent neurodevelopmental outcome. This apparent deleterious effect should be taken into consideration by clinicians when weighing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
186
3
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 341 publications
(210 citation statements)
references
References 21 publications
14
186
3
7
Order By: Relevance
“…Our results thus are in agreement with impaired neurite formation reported earlier at much higher concentrations (Unsicker et al, 1978) and as found more recently in our studies with DEX treatment in vivo, including doses below those in therapeutic use (Kreider et al, 2005a(Kreider et al, , 2006. Effects on this aspect of cell differentiation are likely to contribute to the observation that, even in brain regions that are largely finished with neurogenesis at the time of glucocorticoid therapy, DEX administration elicits reductions in volume (Murphy et al, 2001). Also, in this phase, as was true for undifferentiated cells, high DEX concentrations did not decrease cell viability and actually reduced the proportion of cells showing trypan blue staining.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results thus are in agreement with impaired neurite formation reported earlier at much higher concentrations (Unsicker et al, 1978) and as found more recently in our studies with DEX treatment in vivo, including doses below those in therapeutic use (Kreider et al, 2005a(Kreider et al, , 2006. Effects on this aspect of cell differentiation are likely to contribute to the observation that, even in brain regions that are largely finished with neurogenesis at the time of glucocorticoid therapy, DEX administration elicits reductions in volume (Murphy et al, 2001). Also, in this phase, as was true for undifferentiated cells, high DEX concentrations did not decrease cell viability and actually reduced the proportion of cells showing trypan blue staining.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in mitotic index thus contributes to an actual decline in the number of neural cells, just as observed anatomically with the use of antenatal steroids in animals and humans (Bohn, 1984;Kreider et al, 2005aKreider et al, , 2006Murphy et al, 2001). Furthermore, we did not observe any decrease in cell viability, effectively ruling out the possibility that DEX reduces cell number through cytotoxic actions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, this study had limited data on MRI findings because in the late 90s, MRI was not yet a part of standard clinical care. Therefore, we were not able to associate our findings on GMs with detailed neuroimaging as found previously (23,24). Still, we do not expect to have missed major brain lesions that could have resulted in deterioration of GM quality, as cranial ultrasound is able to detect most abnormalities that are associated with abnormal neurodevelopmental outcome (26,27).…”
Section: Dxm Hcmentioning
confidence: 75%